Los derechos de acceso en asuntos ambientales. Análisis desde experiencias de defensores ambientales en Colombia - Vásquez Santamaría, Jorge Eduardo (2025)
Understanding the obstacles to exercising access rights in environmental matters in Colombia through the lens of democracy is the main objective guiding the question: How have the rights of access to information, participation, and justice in environmental matters been exercised since the enactment of the 1991 Political Constitution? To address this objective, a qualitative and socio-legal methodology was employed, incorporating hermeneutics and phenomenology, with a focus on the experiences of environmental rights lawyers. In-depth semi-structured interviews were conducted to gather information, allowing for the triangulation of experiences that have shaped the realities of environmental defenders. The rights of access to information and environmental participation were used as guiding categories, intersecting with access to justice to form the platform in which the defenders' experiences unfold. From this framework, the study analyzes the shortcomings of the democratic state model in environmental matters.